Vowel Phonemes In Hindi - Sharma, Brahma Dutta; Шарма, Брахма Дутта (Lesya Ukrainka Eastern European National University, 2018)
An analysis of the present day Hindi, as spoken in the northern part of India, brings to light the fact that this language has at least twenty vowel phonemes, and not simply thirteen. Twelve of these twenty vowel phonemes are oral while eight of them are nasalized. Eighteen of them are pure vowels (monophthongs) while two of them are diphthongs. Two of the thirteen vowels included in the current list of alphabet have given place to two consonants with the result that they have ceased to exist. Most of these vowel phonemes occur in all the three positions, namely initial, medial and final, in the Hindi words. Аналіз поточного стану мови гінді, якою розмовляють у північній частині Індії, з’ясовує той факт, що в цій мові є принаймні двадцять голосних фонем, а не три¬надцять. Дванадцять із цих двадцяти породжуються голосом, вісім – назалізовані. Вісім¬надцять з них – чисті голосні (монофтонги), а дві представлено дифтонгами. Дві з тринад¬цяти фонем, що включено до чинного алфавіту, поступилися місцем двом приголосним, а тому зникли з переліку. Більшість зі згаданих голосних зафіксовано в усіх трьох позиціях: на початку, всередині та в кінці слова.
Голосні фонеми в гінді
Keywords: consonants; diphthongs; vowel phonemes; Hindi; monophthongs; meaning; приголосні; дифтонги; голосні фонеми; монофтонги; гінді; значення